PRODUCTION OF PECTINOLYTIC ENZYMES FROM BACTERIAL ISOLATES ASSOCIATED WITH OLIVE (Olea europaea) PLANTS - Yusuf, Hyeladzira Bwala; Emannuel, Samuel A.; Muhammad, Abdulbasid; Jummai, Waye P.; Edith, Ishaku; John, Lugard T.; Nggada, Haruna M. (FUDMA Journal of Sciences, 2025)
Microbial pectinases are widely used in various industries and represent a major class of industrial enzymes. Their broad applications have attracted significant research interest which include plant fiber processing, pectic waste water treatment, paper pulping, fruit juice extraction, and clarification. This study aimed to isolate endophytic bacteria from olive plants and evaluate their potential for pectinase production using the solid-state fermentation (SSF) method. Samples were collected from olive plants in a home orchard located in Zuru, Kebbi State, Nigeria. Bacterial cultures exhibiting the highest zones of inhibition were selected for enzyme production. Orange peel powder served as the pectin-rich substrate in the submerged production medium. Among the isolates, a single pectinolytic strain demonstrated enzyme activity of 1.387 U/mL. These findings suggest that endophytic bacteria associated with olive plants in Zuru have potential as industrial producers of pectinase enzymes.
Keywords: Olive plants; Endophytic Bacteria; Orange peel powder; Pectinase production; Enzyme activity